Perancangan Cinematic Video Sebagai Media Promosi Kampus Ii Stmik Pelita Nusantara Lubuk Pakam - Risa kartika Lubis; Ahmad Zein; Indira Salsabiela (Jurnal Pengabdian kepada Masyarakat Nusantara, 2023)
The background for making cinematic videos as a campus promotional medium is the digital marketing trend during the new normal era. Pelita Nusantara Campus II helps all children of the nation, especially North Sumatran children who wish to study at High Schools to obtain Strata (S1) and Diploma (D3) education certificates. Therefore, the design of promotional media in the form of videos is made because it is effective and displays attractive visual effects with the aim of promoting it again. Pelita Nusantara Campus II. Using a cinematic concept because it can display interesting visual effects and is judged according to campus conditions. packaged through narrative. Video design is carried out using primary data such as observation, interviews and conducting pre-design and post-design surveys. During the project editing process, it is carried out using the Adobe Primary 2020 application. Using the AIDA method (Attention, Interest, Desire, and Action) as a reference, advertising effectiveness needs to meet AIDA elements. The results of this cinematic video will be published on social media such as Facebook, Instagram and YouTube.